درجة امتلاك الباحثين أخلاقيات البحث العلمي في إعداد البحوث بالحفاظ على الحقوق الفكرية وتجنب السرقة العلمية: دراسة ميدانية على عينة من أساتذة التعليم الجامعي - خلاف أمال; طالبي حفيظة (University Of Eloued جامعة الوادي, 2023)
The current study aimed to search for the degree to which researchers possess scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific theft (a field study on a sample of university education professors), based on the following questions: What is the degree of possessing researchers scientific research ethics in preparing Research to preserve intellectual rights and avoid scientific theft?Are there statistically significant differences in the degree of possessing researchers' scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific theft? Are there statistically significant differences in the degree of researchers possessing scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific theft due to the gender variable? Are there statistically significant differences in the degree of researchers possessing scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific plagiarism due to the variable of specialization? During the academic year 2022/2023, the two researchers relied on the descriptive approach. The study was applied to a sample of university education professors. The research tools consisted of a questionnaire about the researchers’ possession of scientific research ethics in preparing research. As for the statistical treatment, it was done using Pearson’s correlation coefficient and Cronbach’s alpha coefficient., and the "T" test, and one-way variance, the results showed that the degree of researchers' possession of scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific theft was high, and the results of the study indicated that there were statistically significant differences in the degree of researchers' possession of scientific research ethics inPreparing research by preserving intellectual rights and avoiding scientific theft, and the presence of statistically significant differences in the degree of possession of scientific research ethics by researchers in preparing research by preserving intellectual rights and avoiding scientific theft due to the gender variable. The results of the study concluded that there were no statistically significant differences in the degree of possession Researchers The ethics of scientific research in preparing research by preserving intellectual rights and avoiding scientific theft is attributed to the variable of specialization.
The degree to which researchers possess scientific research ethics in preparing research by preserving intellectual rights and avoiding scientific plagiarism: a field study on a sample of university education professors
مداخلة
Keywords: الباحث; أخلاقيات البحث العلمي; أساتذة التعليم العالي; researcher; scientific research ethics; university education professors